Strategic Management of the Socio-Economic Development of Macro Systems of Public and Regional Levels - Марич, Максим; Kozak, Kateryna; Liudmyla, Pankova; Olesya, Finagina; Vitaliy, Bulyuk; Serhiy, Rybalko (My University, 2022)
The article is devoted to the study of the features of strategic management of socio-economic development of macro systems at the state and regional levels. The essence and structure of macro systems of state and regional levels are studied. It was found that a macro system consists of microsystems, which are its elements and in turn are characterized by complexity, diversity and different functionality. It is established that the allocation of macro system boundaries depends on certain conditions, circumstances and goals, and the process of establishing them is determined by a number of features, which distinguish geographical, regional, economic, political and market boundaries. The main conditions and factors influencing the process of forming and choosing a strategy for socioeconomic development of the macro system are identified, among which are: spatial and temporal boundaries, form of government, characteristics of a particular object, subject and object of management, the level of various resources. It is proved that the main feature of strategic management of macro systems is that it is based on forecast models and macroeconomic indicators for the application and receipt of which requires forecasting.
Keywords: strategy; management; strategic management; socio-economic development; macro systems; state-level macro system; regional macro system